DISCOVERING RELATIONSHIP BETWEEN SOCIAL MEDIA USAGE AND CYBERSECURITY AWARENESS: AN ASSOCIATION MINING ANALYSIS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The term cyber security pertains to the  protection of computer systems, networks,  devices, data, and other related entities from  potential threats, hazards, or assaults. The level  of awareness of cyber security pertains to the  extent to which a user possesses knowledge  regarding the potential threats that may  compromise the security of their network.  In contemporary times, the utilization of  social media platforms has witnessed a  significant surge, thereby raising apprehensions  regarding the safety of online activities  and the perpetration of cyber offenses. The  aforementioned circumstance necessitates the  implementation of cyber security measures  in conjunction with the cultivation of a  positive digital social environment. Despite  the convenience of accessing information  from any location, there exists a potential  risk of unauthorized disclosure of personal  data to unintended recipients. Despite the  prevalence of cybercrime as a significant  threat to individuals, a considerable number  of individuals remain unaware of its existence.  Despite the fact that security is a subject that is  addressed in distinct modules within numerous  general computer science programs, it remains  uncertain whether the implementation of  cyber security measures is necessary. The  objective of this research is to examine the  correlation between the utilization of social  media platforms and the level of consciousness  regarding cybercrimes among individuals. The  research employed the Apriori algorithm to  detect associations, and the findings indicated  robust associations among various variables  pertaining to knowledge of cyber security.  The statistical significance of the associations  was evaluated through the utilization of three  metrics, namely confidence, lift, and leverage.  The results of the study could be utilized  to enhance the knowledge of social media  users regarding cyber security and emphasize  the significance of staying up-to-date with  cybercrimes and safeguarding oneself while  utilizing social media platforms.
Keywords: Cyber security; social media; social media sites; cyber-attacks; Cybercrime; Association mining; apriori